Exploring the Mechanisms of Self-Control Improvement. (August 2014) - Inzlicht, Michael; Legault, Lisa; Teper, Rimma
Good self-control is central to success across life domains, from school to work to relationships. In this article, we provide a framework to better understand how self-control can be improved. Using cybernetic principles, we identify and integrate important mechanisms for self-control improvement that have previously been overlooked. The cybernetic model suggests that control relies on three separate processes: setting goals, monitoring when behavior diverges from goals, and implementing behavior aligned with goals. Within each of these stages, we incorporate recent research identifying key features of good self-control, including setting the "right kind" of goals; the role of conflict detection, attention, and emotional acceptance in goal monitoring; and the effects of fatigue, shifting priorities, and intentions on implementing behavioral changes. Self-control is not easy, but by revealing it as reliant on these diverse processes, we offer a more comprehensive perspective on self-control, as well as routes through which it can be improved.